German Corporate Profits: 1926-1938 - Sweezy, Maxine Yaple (Quarterly Journal of Economics, 1940)
Nature of the data, 384. — Scope of the study, 385. — Method of computation, 386. — The small business man not included, 387. — General movement of profits, 387. — Influence of the two Four-Year Plans, 388. — Comparison of industries, 389. — The problem of new financing, 395. — Provisional figures for 1937 and 1938, 396. — Objections: profits may not mean what they say, 397; disposal over profits is not free, 397. — Adjustment for taxes, 398.